2006
DOI: 10.1007/s11099-006-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of photosystems 2 and 1 during leaf growth in grapevine seedlings probed by chlorophyll a fluorescence transient and 820 nm transmission in vivo

Abstract: Chlorophyll (Chl) a fluorescence transient and 820-nm transmission kinetic were investigated to explore the development of photosynthetic apparatus in grapevine leaves from emergence to full expansion. In this study, all leaves at various developing stages exhibited typical Chl a fluorescence transient. In newly initiating leaves, the maximum quantum yield of primary photochemistry (φ P0 ) was slightly lower (<10 %) than that in fully expanded leaves. Nevertheless, the fluorescence rise from O to J step was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
(17 reference statements)
5
16
0
4
Order By: Relevance
“…Performance index PI abs is found to be a very sensitive parameter in different crops and in most of environmental stress situations (Strasser et al 2000, Jiang et al 2006, Christen et al 2007, Oukarroum et al 2007, which is in accordance with our results achieved on winter wheat plants under drought stress. Van Heerden et al (2007) observed also a very good positive correlation between CO 2 assimilation capacity and PI abs values under water stress.…”
Section: Resultssupporting
confidence: 92%
“…Performance index PI abs is found to be a very sensitive parameter in different crops and in most of environmental stress situations (Strasser et al 2000, Jiang et al 2006, Christen et al 2007, Oukarroum et al 2007, which is in accordance with our results achieved on winter wheat plants under drought stress. Van Heerden et al (2007) observed also a very good positive correlation between CO 2 assimilation capacity and PI abs values under water stress.…”
Section: Resultssupporting
confidence: 92%
“…In contrast to PSII, less attention was paid to PSI activity during leaf growth. Only a few functional PSIs were observed to be developed at the initial stages of leaf growth in grapevine, but it matched perfectly with PSII (Jiang et al 2006c). It should be noticed that young leaves are more susceptible to photodamage, since excited energy captured by light harvesting complexes is less spent on promoting the carbon assimilation.…”
Section: Introductionmentioning
confidence: 83%
“…J-step appears because accumulation of Q A -reaches the maximal level, and Vj can be used to reflect the change of J-step (Strasser et al 2004). Jiang et al (2006c) detected a higher K-step in young leaves of grapevine, and it was explained that the functional connection between OEC and PSII was not fully built at the beginning of leaf growth. However, Vk was not higher in NIL than that in NEL or EL (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations